In situ synthesis of C-TiO2/g-C3N4 heterojunction nanocomposite as highly visible light active photocatalyst originated from effective interfacial charge transfer - Lu, Zhao; Zeng, Lei; Song, Wulin; Qin, Ziyu; Zeng, Dawen; Xie, Changsheng (Applied catalysis. B, Environmental, 2017)
[Display omitted] •One pot hydrothermal method was adopted to prepare C-TiO2/g-C3N4 nanocomposite with high visible light photocatalytic activity.•The mechanism was enhancement of visible light absorption and fast separation of electron-hole pairs.•Interfacial charge transfer through CTi bond and NTi bond played a crucial role in separation of electron-hole pairs.•Active species h+, O2−, OH were all generated in the photocatalytic process and O2− played a significantly important role. In this paper, a simple one-pot hydrothermal strategy was adopted to prepare C-TiO2/g-C3N4 nanocomposite. Simultaneously, the photocatalytic performance of the C-TiO2/g-C3N4 nanocomposite like tunable ratio was evaluated by the degradation of methyl orange (MO) under visible light irradiation. The prepared nanocomposite with the mass ratio of 27:8 (C-TiO2/g-C3N4(0.08)) possessed the highest photocatalytic activity, about 5.1, 3.8 and 2.3 times higher than that of C-TiO2, g-C3N4, and the Mixing sample, respectively. The excellent photocatalytic performance was attributed to the improvement of light harvesting and charge separation caused by construction of heterojunction. In addition, interfacial charge transfer through CTi bond and NTi bond also played a crucial role in inhibiting the recombination of electron-hole pairs and increasing the concentrations of holes and electrons, separately, which was confirmed by XPS analysis, photocurrent response experiment, electrochemical impedance spectroscopy measurements, PL spectra and Time-resolved PL spectra. Besides, the importance of active species during the reaction process was explored, and the generation of h+, O2−, OH in the photocatalytic process was also demonstrated. Among this, O2− played an important role. This finding about chemically bonded C-TiO2/g-C3N4 nanocomposite provided a good guidance for the fabrication of new heterogeneous photocatalysts and facilitated their applications in environmental protection, water splitting and so on.